Design and testing of the safety of the SARUS-CPR hood for novice resuscitators. Issue 4 (November 2022) - Wasik, P.; McLeod, G. A.; Mountain, R.; Watts, S.; Briggs, H.; Maini, N.; Belford, I.; McGuire, B.; Brown, W.; Clark, R.; Eley, I; Richardson, E.; et al.
Background and aims: Bystanders should be protected against aerosols, droplets, saliva, blood and vomitus during resuscitation after cardiac arrest The SARUS (safer - airway - resuscitation) CPR airway hood™ is a clear plastic cover and integrated mask that envelopes the head and torso. Our objectives were to test leakage using saline aerosol generation tests, then assess the performance of the hood during mock cardio-pulmonary resuscitation on a manikin. Methods: A checklist was validated by comparing the performance of 10 novices against 10 experts during mock resuscitation. Thereafter, 15 novices were tested with and without the hood, in a randomised cross-over study, one week apart. Results: Laboratory analysis showed a > 99% reduction of saline particles detected 5 cm, 75 cm and 165 cm above volunteers wearing the hood. On manikins, experts scored better compared to novices, 8.5 (0.7) vs 7.6 (1.2), difference (95%CI) 0.9 (0.4–1.3), P = 0.0004. Novice performance was equivalent using the hood and standard equipment, 7.3 (1.4) vs 7.3 (1.1) respectively, difference (90%CI) 0.0 (−0.3 - 0.3), P = 0.90. Conclusion: Aerosol transmission reduced in the breathing zone. Simulated resuscitation by novices was equivalent with and without the hood.